Perancangan User Interface dan User Experience pada Aplikasi Pencari Indekos - Gusto Gibeon Ginting; I Gusti Ngurah Anom Cahyadi Putra (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
This study aims to design a website-based user interface and user experience. Where it is, proportional to the increase in the number of purchases of existing motorcycles. The website that has been made was tested on the General Public with a total of 20 respondents. To find out the level of satisfaction of respondents in using the motorcycle recommendation website, usability testing was carried out using the system usability scale method. This method measures the usability of a computer system according to the user's subjective point of view by filling out a Likert-scale questionnaire. The website that has been made is tested on the General Public. To find out the level of satisfaction of respondents in using the motorcycle recommendation website, usability testing was carried out using the system usability scale method. This method measures the usability of a computer system according to the user's subjective point of view by filling out a Likert-scale questionnaire.